Biking to School: The Role of Bicycle‐Sharing Programs in Adolescents. (4th November 2018) - Estevan, Isaac; Queralt, Ana; Molina‐García, Javier
ABSTRACT: BACKGROUND: The purpose of this study was to: (1) describe modes of transport to school, with a specific focus on the use of public bicycle share programs (PBSP); and (2) assess sociodemographic, psychosocial, and environmental correlates of bike and PBSP use to go to school. METHODS: A group of 465 adolescents from the International Physical Activity and the Environment Network (IPEN) Adolescent Study (Valencia, Spain) participated in the research. Mixed regression analyses were conducted on the data obtained. RESULTS: Not having bicycle access, a PBSP card, or a public bike lane close to the school is negatively associated with bicycle use. PBSP is positively associated with physical self‐efficacy and bicycle availability and negatively associated with the number of vehicles per drivers at home and not having PBSP stations close to the school. CONCLUSIONS: The strongest predictive factor, as regards cycling as an active mode of transport to school among adolescents is having a PBSP card. Schools have a crucial role in promoting bicycle use through collaboration when designing public policies that consider access to bike lane networks and PBSP stations and therefore should encourage local government implementation policies and/or increase PBSP stations within 250 m of the school.